Recent Developments in Railway Track and Transportation Engineering Proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on Sustainable Civil Infrastructures (Sustainable Civil Infrastructures,, 2018)
This volume brings together scientific experts in different areas that contribute to the Railway Track & Transportation Engineering challenges, evaluate the State-of-the-Art, identify the shortcomings and opportunities for research and promote the interaction with the industry. In particular, scientific topics that are addressed in this volume include railway ballasted track degradation/settlement problems and stabilization/reinforcement technologies, switches and crossings and related derailments causes, train-induced vibrations and mitigation measures, operations, management and performance of ground transportation, and traffic congestion and safety procedures. This volume is part of the proceedings of the 1st GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2017.